A Narrative Review on Evaluation of Causal Drug in Cutaneous Drug Eruptions: Challenges, Current State, and the Path Ahead - Sivaranjini Ramassamy (International Journal of Advanced Medical and Health Research)
The diagnosis of cutaneous drug reactions is challenging, particularly when it involves the identification of the culprit drug. This exercise is, however, essential, as re-prescription of the offending drug is harmful to the patient while holding back an essential drug for the fear or suspicion of an allergy could result in a less effective second line or an expensive alternative, both of which are undesirable. We need to be aware of the standard systematic approaches to the diagnosis of drug hypersensitivity and be familiar with the extant guidelines to inform clinical decision making. The clinical tools available for a definite diagnosis are a clinical history, standardized skin tests, drug challenge, and a few biological tests that are in the pipeline. An understanding of the basis for each of these with the steps involved, interpretations, and limitations is important for optimal practice. This review will highlight the key messages concerning the role of each of these tools available for the identification of causal drugs in drug hypersensitivity with the challenges involved in their application, plausible solutions, and the way forward.